A study on liquidity performance of top performing indian manufacturing companies - S, POORNIMA; M, THEIVANAYAKI (Journal of Management and Science, 2012)
The term liquidity probably brings to mind the relationship of current assets to current liabilities. However, the concept of liquidity should encompass much more than simply these two balance sheet accounts. This study is based on previous ten years Annual Reports of the top performing manufacturing companies in India. In this study, liquidity is taken to mean the short term liquidity which refers to the ability of the firms to pay off the current liabilities. This study relates to the management of short term assets and liabilities and finding the relationship between liquidity, profitability and leverage measures of a firm.Short term liquidity has been considered crucial to the very existence of an enterprise. This will further lead to financial distress and finally corporate can go bankrupt. The conflict arises because the maximization of firm’s returns could seriously threaten the liquidity and on the other hand, the pursuit of liquidity has a tendency to dilute returns. The result can determine the risk postulate to that future customer. Additionally, this result can be utilized as a yearly appraisal of financial situation in making decisions to invest in the corporate. The result can contribute in advance an indication of the financial situation to aid the investor’s selection of companies.